If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4m + 8m = 5 + 3m Combine like terms: -4m + 8m = 4m 4m = 5 + 3m Solving 4m = 5 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. 4m + -3m = 5 + 3m + -3m Combine like terms: 4m + -3m = 1m 1m = 5 + 3m + -3m Combine like terms: 3m + -3m = 0 1m = 5 + 0 1m = 5 Divide each side by '1'. m = 5 Simplifying m = 5
| 3m+=-3-2m | | d^2=46 | | 34x=170 | | 20d-18d=12 | | (13b-6)-3(4b+3)=-3 | | 2s+s=12 | | 1-2x=6-2x | | -n+25=-2(4n+5) | | 1.25r+1.25(r+4)=40 | | 8x+12=67+3x | | (2x)=(5x-1) | | 10p-4p=12 | | 14x+2y=18 | | s^2-15s=0 | | 8a^2+11a-8=0 | | 8u+4-2(-4u-2)=2(u-2) | | z=34580+(-6110.84)ln(1850) | | (0.625x+7)=(11-x) | | 2x-16+x-8+x=180 | | -7x-5y=-20 | | -3+-5=34 | | 3-5=34 | | y=-160+-9(-9) | | -n^2-15n=0 | | -y=-2+3x | | 3x(2x-1)(x+7)=0 | | (2x+1)+(1-3y)=-1-2i | | 2x-(4x+6)=2 | | 2x+4x-12=6 | | 20(-2.25)-5y=30 | | 13-r=7+2r | | 5y-5-3x=0 |